2020
DOI: 10.1093/cid/ciaa824
|View full text |Cite
|
Sign up to set email alerts
|

Measles, Mumps, Rubella, and Varicella Zoster Virus Serology and Infections in Solid Organ Transplant Recipients During the First Year Posttransplantation

Abstract: Background Mumps, measles, rubella, and varicella zoster (MMRV) viruses may cause severe infections in seronegative adult solid organ transplant (SOT) recipients, but can be prevented by vaccination. We aimed to determine MMRV serostatus in adult SOT recipients before and 1 year after transplantation as well as evidence of MMRV infections in a large, prospective cohort of SOT recipients. Methods This was a prospective study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…as examples of absolute correlation towards clinical protection (i.e., seroprotection almost guarantees protection) [63]. In line with this, a study in Denmark has included lung transplant patients and analyzed serostatus prior to transplantation and one-year posttransplant [78]. Approximately 13% of lung transplant patients were seronegative to at least one of the MMR viruses prior to transplantation.…”
Section: Measles Mumps and Rubellamentioning
confidence: 99%
See 1 more Smart Citation
“…as examples of absolute correlation towards clinical protection (i.e., seroprotection almost guarantees protection) [63]. In line with this, a study in Denmark has included lung transplant patients and analyzed serostatus prior to transplantation and one-year posttransplant [78]. Approximately 13% of lung transplant patients were seronegative to at least one of the MMR viruses prior to transplantation.…”
Section: Measles Mumps and Rubellamentioning
confidence: 99%
“…Among the recipients that remained seronegative for at least one year, 43% remained seronegative and 57% seroconverted during follow up. Additionally, lung transplant recipients were found to be more likely to seroconvert, which was hypothesized due to the transfer of antibodyproducing long-lived plasma cells from a seropositive donor lung [78]. It should be kept in mind that measles and mumps vaccines are live-attenuated and are therefore contraindicated after lung transplantation…”
Section: Measles Mumps and Rubellamentioning
confidence: 99%
“…Another study from Denmark showed a higher seroprevalence of measles (95.3%), mumps (89%), rubella (90.7%), and VZV (96.3%) among 1182 SOT candidates. 11 These studies, including ours, identified younger age as a factor associated with seronegativity. 11,23 The timing of the introduction of MMR vaccines in individual countries (United States: 1971 24 and Denmark: 1987 25 ) could explain why elderly patients have higher seropositivity, which is likely caused by natural infection.…”
Section: Discussionmentioning
confidence: 53%
“…The concept of the transfer of cells, cell fractions and molecules is increasingly recognized as a common feature of organ transplantation [3][4][5]19]. PLS is seen as an active form of this and has been seen as donor B cell production of antibodies against recipient antigens, typically against ABO antigens on red blood cells, leading to hemolytic anemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…Koshizuka et al have also shown that donor-derived plasma cells transmitted in a lung allograft are capable of producing long lasting anti-cytomegalovirus antibodies [5]. Rezahosseini et al have extended this concept further with a recent paper noting that at 1 year post organ transplant 57% of seronegative recipients show seroconversion for at least one of measles, mumps or rubella viruses without clinical infection [19]. Put together these PLS case series make it quite likely that the current study is yet another PLS example-and does not represent recipient HCV infection perse.…”
Section: Discussionmentioning
confidence: 99%